The The Development of the Research Management System of National University of Laos - Bouasangthong, Vannasouk; Thalangsy, Khamseng; Leusinxay, Intong (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study aimed to develop the research management system at the National University of Laos (NUOL) through a structured research and development approach, conducted in four phases. Phase one defined the components and indicators of NUOL's research management system, involving nine administrators from the Research Office and Research and Academic Service Division. Phase two assessed the current system, surveying 306 administrators and faculty members across 13 faculties. In phase three, an optimized system was developed with input from 17 key figures, including NUOL's vice president, research division heads, and national research committee members. Phase four evaluated the system with 48 participants, including division heads and faculty staff. Data collection involved semi-structured interviews and questionnaires, analyzed using frequency, percentage, means, standard deviation, interquartile range, and content analysis. Findings revealed: NUOL’s research management system comprises four components and 65 indicators: 14 for input, 42 for process (5 sub-processes), 5 for output, and 4 for feedback. The current system showed suitable input but faced challenges like budget constraints and unstructured research guidance. Processes were applied consistently but had monitoring, evaluation, and utilization issues. Outputs were satisfactory but required improved reliability, while feedback practices faced challenges. The optimized system includes four components with 61 indicators: Input (13), Process (40 across 5 sub-processes), Output (4), and Feedback (4). Evaluation results indicated that the system achieved the highest utility and feasibility ratings and high propriety and accuracy ratings. In conclusion, the developed system with 61 indicators across four elements was validated by research experts, addressing challenges in implementation and improving research management effectiveness at NUOL.